Challenges in the Treatment of Urinary Tract Infections: Antibiotic Resistance Profiles of Escherichia coli Strains Isolated from Young and Elderly Patients in a Southeastern Romanian Hospital - Andreea-Elena Topa; Constantin Ionescu; Anca Pinzaru; Elena Mocanu; Ana Maria Iancu; Elena Dumea; Bogdan Florentin Nitu; Florin Gabriel Panculescu; Simona Claudia Cambrea (Biomedicines)
Background/Objectives: Urinary tract infections (UTIs) represent a significant public health challenge, with Escherichia coli being the primary causative pathogen. The rise in antimicrobial resistance (AMR), further intensified by shifts in antibiotic prescribing practices during and after the COVID-19 pandemic, poses substantial difficulties in treatment optimization and clinical management. Methods: This retrospective study analyzed 644 E. coli strains from urine samples collected in a southeastern Romanian hospital during two periods: pre-pandemic (2018–2019, N = 361) and post-pandemic (2023–2024, N = 283). Antimicrobial susceptibility was assessed using the VITEK automated system for key antibiotic classes. Results: A significant increase in fluoroquinolone resistance was observed, especially for ciprofloxacin (p = 0.02), alongside rising ceftriaxone resistance (p = 0.004), suggesting the spread of ESBL-producing strains. Resistance to trimethoprim/sulfamethoxazole, ampicillin, and amoxicillin/clavulanic acid remained high, limiting their empirical use. Carbapenem resistance was low (p > 0.1), while nitrofurantoin and fosfomycin retained high efficacy (p = 0.26 and p = 0.64). Conclusions: The post-pandemic period showed a concerning rise in resistance to fluoroquinolones and third-generation cephalosporins, highlighting the need for stricter antimicrobial stewardship. Carbapenems remain effective for severe infections, while nitrofurantoin and fosfomycin are reliable first-line options for uncomplicated UTIs. Continuous AMR surveillance is essential to optimize treatment and curb multidrug-resistant strains.